2012
DOI: 10.1002/hed.22946
|View full text |Cite
|
Sign up to set email alerts
|

Voice and swallowing after partial laryngectomy: Factors influencing outcome

Abstract: Horizontal supraglottic laryngectomy and supracricoid partial laryngectomy give the same swallowing results. The presence of both arytenoids does not influence the final outcome compared to patients in whom only 1 arytenoid is preserved. Postoperative radiotherapy only influences the swallowing function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Alicandri-Ciufelli et al have reported that the type of partial laryngectomy does not seem to affect the deglutition results, whereas radiotherapy significantly and negatively affected the dysphagia score [8] . To our knowledge, the present study is the second in the literature to evaluate postoperative functions between SGHL and SCPL.…”
Section: Discussionmentioning
confidence: 99%
“…Alicandri-Ciufelli et al have reported that the type of partial laryngectomy does not seem to affect the deglutition results, whereas radiotherapy significantly and negatively affected the dysphagia score [8] . To our knowledge, the present study is the second in the literature to evaluate postoperative functions between SGHL and SCPL.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of this literature search result from our inclusion and exclusion criteria. A lot of studies were excluded because of their limited patient population, whereas a few studies were excluded because TNM stage was not well documented or the study was published in or before 1990 …”
Section: Discussionmentioning
confidence: 99%
“…Some authors defend that the decanulation time 1,26,36 , the concomitance with adjuvant therapies such as radiotherapy 6,10,11,37 , the patient age 5,8,9,38 , and the performance of cervical esvaziation 11 are factors that influence on general quality of life, affecting emotional and socials aspects 12,16 . Early decanulated patients are more satisfied with their quality of life than those who remained with the tracheostomy for a long period of time 11,13,26,38 , since besides affecting directly the feeding and increasing the permanence in hospital 35 , the presence of the tracheal cannula affects significantly the voice, contributing for a difficulty in the speech intelligibility with a consequent prejudice in social communication¹.…”
Section: Sewnaikmentioning
confidence: 99%
“…Early decanulated patients are more satisfied with their quality of life than those who remained with the tracheostomy for a long period of time 11,13,26,38 , since besides affecting directly the feeding and increasing the permanence in hospital 35 , the presence of the tracheal cannula affects significantly the voice, contributing for a difficulty in the speech intelligibility with a consequent prejudice in social communication¹. Thus, patients tend to have a better self-assessment of quality of life when they are without the nasogastric tube, decanulated and with the possibility of social eating 7,8,26,37 .…”
Section: Sewnaikmentioning
confidence: 99%